Sex Disparities in the Management and Outcomes of Cardiogenic Shock Complicating Acute Myocardial Infarction in the Young - Vallabhajosyula, Saraschandra (Circ Heart Fail, 2020)
BACKGROUND: There are limited data on how sex influences the outcomes of acute myocardial infarction-cardiogenic shock (AMI-CS) in young adults. METHODS: A retrospective cohort of AMI-CS admissions aged 18–55 years, during 2000–2017, was identified using the National Inpatient Sample. Use of coronary angiography, percutaneous coronary intervention (PCI), mechanical circulatory support (MCS) and non-cardiac interventions was identified. Outcomes of interest included in-hospital mortality, use of cardiac interventions, hospitalization costs, and length of stay. RESULTS: A total 90,648 AMI-CS admissions ≤55 years of age were included, of which 26% were women. Higher rates of CS were noted in men (2.2% in 2000 to 4.8% in 2017) compared to women (2.6% in 2000 to 4.0% in 2017) (p<0.001). Compared to men, women with AMI-CS were more frequently of black race, from a lower socio-economic status, with higher comorbidity, and admitted to rural and small hospitals (all p<0.001). Women had lower rates of ST-segment elevation presentation (73.0% vs. 78.7%), acute non-cardiac organ failure, cardiac arrest (34.3% vs. 35.7%), and received less frequent coronary angiography (78.3% vs. 81.4%), early coronary angiography (49.2% vs. 54.1%), PCI (59.2% vs. 64.0%), and MCS (50.3% vs. 59.2%) (all p<0.001). Female sex was an independent predictor of in-hospital mortality (23.0% vs. 21.7%; adjusted odds ratio 1.11 [95% confidence interval 1.07–1.16]; p<0.001). Women had lower hospitalization costs (156,372±198,452 vs. 167,669±208,577; p<0.001) but comparable lengths of stay compared to men. CONCLUSIONS: In young AMI-CS admissions, women are treated less aggressively and experience higher in-hospital mortality than men.